The Hyperreality of Identity Politics on Social Media - Hariyanto, Didik; Dharma, Ferry Adhi; Yussof, Ishak; Muharram, Fajar (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
Religious-based identity political content is widespread on social media, raising voter polarization and social conflict. This research revealed the religious commodification of political buzzers for political identity and the hyperreality created on social media to attack their political opponents with identity politics. It used a qualitative commodification perspective by Jean Baudrillard. The data source was identity political content produced by buzzers from 03 October 2022 to 03 May 2023 or since the NasDem Party declared Anies Baswedan a presidential candidate. The results suggested that political buzzers coordinatedly use religion as a political commodity to build hatred through the Kadrun hashtag. In the 2019 elections, this hashtag successfully created a radical stigma among groups supporting Prabowo-Sandi and is now used to attack Anies supporters. Besides, the hyperreality created by the buzzers is the symbolization of Arab Islam to label Anies and his supporters, and indigenous Islam to describe cultural Islamic groups or native Indonesian Islam. Through social media, Arab Islam is simulated as a group full of conflict and supporting the caliphate while indigenous Islam is a peace-loving and nationalist group, which leads to widespread social disintegration, not only among Muslims in the country but also sentiment among Arab descendants in Indonesia. The impact of extreme identity politics can encourage radicalization and violence, especially when there are narratives that manipulate feelings of injustice or threats to the identity of certain groups.